Analysis of Land Use Patterns in the Kampung Minang Tourism Village, Nagari Sumpur, Based on Geographic Information Systems (GIS) - Tengku Abdillah Azis; Delon A.L Sitompul; Maria Joito Gultom; Cindy Melissa Wijaya; Wiji Syahfitri; Tumiar Sidauruk (Asosiasi Dosen Muda Indonesia, 2025)
The method used is descriptive quantitative, with primary data collected through field observations and interviews, and secondary data obtained from drone imagery and spatial planning documents. The analysis involved land classification, thematic mapping, and Nearest Neighbor Analysis (NNA). The results show that land use is dominated by sapodilla plantations (48.89%) and rice fields (33.86%), reflecting the village’s agrarian character. Regional facilities are evenly distributed, supporting educational, health, and cultural functions. The NNA indicates a clustered settlement pattern, with a Nearest Neighbor Ratio of 0.329755 and a z-score of -28.470036, signifying concentrated residential areas due to geographical factors and accessibility. These findings emphasize the importance of spatial planning in sustainable tourism village development.